2003
DOI: 10.1785/0120010230
|View full text |Cite
|
Sign up to set email alerts
|

Fault Structure Control on Fault Slip and Ground Motion during the 1999 Rupture of the Chelungpu Fault, Taiwan

Abstract: The Chelungpu fault, Taiwan, ruptured in a M w 7.6 earthquake on 21September 1999, producing a 90-km-long surface rupture. Analysis of core from two holes drilled through the fault zone, combined with geologic mapping and detailed investigation from three outcrops, define the fault geometry and physical properties of the Chelungpu fault in its northern and southern regions. In the northern region the fault dips 45Њ-60Њ east, parallel to bedding in both the hanging wall and footwall, and consists of a narrow (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 48 publications
9
87
0
2
Order By: Relevance
“…In fact, Schultz and Evans [1998, their figure 16] showed that the width of a single fault's DZ can vary by an order of magnitude depending on which deformation elements are used to define the DZ. Furthermore, the DZ is often asymmetric around the FC and PSZ [e.g., Shipton and Cowie, 2001;Heermance et al, 2003;Dor et al, 2005]. The dominant deformation elements within each part of the fault zone may also change over time, for instance due to varying stress conditions [Knipe and Lloyd, 1994] or rock rheology [Johansen et al, 2005].…”
Section: Figure 3 Discussion and Conclusionmentioning
confidence: 99%
“…In fact, Schultz and Evans [1998, their figure 16] showed that the width of a single fault's DZ can vary by an order of magnitude depending on which deformation elements are used to define the DZ. Furthermore, the DZ is often asymmetric around the FC and PSZ [e.g., Shipton and Cowie, 2001;Heermance et al, 2003;Dor et al, 2005]. The dominant deformation elements within each part of the fault zone may also change over time, for instance due to varying stress conditions [Knipe and Lloyd, 1994] or rock rheology [Johansen et al, 2005].…”
Section: Figure 3 Discussion and Conclusionmentioning
confidence: 99%
“…Field observations of maturely slipped faults show a generally broad zone of damage by cracking and granulation (Chester et al, 1993), but nevertheless suggest that shear in individual earthquakes takes place with extreme localization to a long-persistent slip zone, <1-5 mm wide, within or directly bordering a finely granulated, ultracataclastic fault core (Chester and Chester, 1998;Chester at al., 2003, 2004. Heermance et al, 2003Wibberley and Shimamoto, 2003).…”
Section: Fault Zone Structure Friction and A Quandary In Seismologymentioning
confidence: 99%
“…The fault plane lies at the contact point of shale and conglomerate in the south but within the Chinshui Shale in the region of large displacements (Huang et al 2002). In this regard, the physical properties of the fault-zone material and width and roughness of the fault zone probably vary considerably along the fault, and this heterogeneity may play an important role for the above mechanisms to operate during the rupture propagation Heermance et al 2003).…”
Section: Introductionmentioning
confidence: 99%